Strategies for change: exploring the impact of the 2004 nationality law reform campaign on gender equality in Egypt - MacKay, Catherine (AUC Knowledge Fountain, 2012)
Prior to 2004 Egyptian law allowed for conferral of nationality by paternal descent only, with few exceptions. By barring Egyptian women from passing their nationality to their children, such legislation reflected a belief that women were in fact not full members of the national political community on an equal footing with men. Facing pressure from both internal and external sources, the Egyptian government reformed the law in 2004, thereby allowing women to confer their nationality on their children. Yet nearly eight years later many children eligible for Egyptian nationality have yet to acquire it, and Egyptian women are arguably no closer to being acknowledged as full and active citizens of their own country. This reality brings the success of this and other legal reform efforts addressing gender inequality into question. This research project aims to explore the intersections of law, citizenship, gender-based discrimination and social reform movements as played out in the case of Egypt's 2004 nationality law reform. It is framed within an understanding of citizenship as the active participation of the individual in the public life of the community, and advances the notion that for women to be considered as citizens on an equal footing with men requires that they be afforded the opportunity, space and resources to become active participants. It further examines the role of law in social reform movements, questioning whether the â successâ of reform movements is to be found in the writing of new law itself, in improved implementation and enforcement of law, in increased social mobilization, or in a combination thereof. Finally, through interviews with Egyptian pro-reform advocates, it analyzes the 2004 nationality law reform with a view to understanding the mixed success of legal reform movements attempting to combat deep-seated patterns of social discrimination, and explores the reformers' choice of tactics and the impact of these choices on the ultimate achievement of their broader goal of gender equality.